2019
DOI: 10.1371/journal.pone.0218961
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia and its associated factors among children under five years of age attending at Guguftu health center, South Wollo, Northeast Ethiopia

Abstract: Background Anemia during childhood adversely affects mental, physical and social development of the children. This study is aimed to assess the prevalence of anemia and its associated factors among children less than five years of age in Guguftu, South Wollo, Northeast Ethiopia. Method A cross-sectional health facility based study was conducted among 404 children aged 6 to 59 months. Systematic random sampling technique was used to include the participants. Pretested an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
109
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(181 citation statements)
references
References 31 publications
35
109
1
9
Order By: Relevance
“…In addition, the Ghana Living Standard Survey Round 7 report suggests that the Northern, Upper East and Upper West Regions are leading poor regions in Ghana [ 39 ]. These findings are also supported by prior studies [ 2 , 40 ]. In this regard, poverty reduction should be considered as part of the strategies to eradicate anaemia in Ghana.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, the Ghana Living Standard Survey Round 7 report suggests that the Northern, Upper East and Upper West Regions are leading poor regions in Ghana [ 39 ]. These findings are also supported by prior studies [ 2 , 40 ]. In this regard, poverty reduction should be considered as part of the strategies to eradicate anaemia in Ghana.…”
Section: Discussionsupporting
confidence: 92%
“…A cross-sectional survey on pediatric anaemia in rural Ghana also found that younger age was a risk factor of anaemia [ 37 ]. In Ethiopia, [ 2 ] revealed that children of low socio-economic status were five times more likely to be anaemic compared to children of high socio-economic status. These findings may be explained by poverty-related malnutrition [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other factor strong association with both anemia and severe anemia is the wealth status of the family. The child with poor family highly affected by anemia and severe anemia this output in line with other ndings done in different areas [37][38][39][40]. This nding could be due to the reason for problems in production or purchasing necessary food for themselves and their children, so they can not get iron-rich foods.…”
Section: Model Comparisonsupporting
confidence: 83%
“…Some previous studies espoused that there is a direct link between food consumption and anaemia. Due to this, in household where there is no food security, it can affect the nutritional status of children, which could contribute to anaemia (Ali et al, 2013;Gebreweld, Ali, Ali & Fisha, 2019). Relatedly, we found that children in large households had higher odds of suffering from anaemia compared to those in small household.…”
Section: Discussionmentioning
confidence: 62%